Saúde mental e atenção primária: compreendendo articulações e práticas de cuidado na Saúde da Família no Ceará. - Viana, Diego Mendonça (2016)
This dissertation is configured as one of the border area of research initiatives in public health policy, ie it consists of a scientific effort to understand the relationship between the field of Primary Health Care (PHC) and the field of Mental Health (SM) in the territories. The main objective of the research was to understand the care practices developed by professionals in the Family Health Strategy (FHS) in the state of Ceará to the demands of mental health exist in the teams responsible for territories. The methodology is situated in the field of qualitative research in public health and this study is configured as cross as to time and in an exploratory perspective on the findings of its object. The research scenarios were composed of health facilities linked to the Family Health Strategy (FHS) in the cities of Fortaleza and Iguatu, State of Ceara. The research subjects were the professionals of the Family Health Reference Team (EQRSF) and Support Center for Family Health (NASF). Data collection was done by interviews semi-structured individual and collective. Data analysis was done using the theoretical framework of content analysis and interpretation made light of Dialectical Materialism History. The research followed all appropriate ethical procedures and recommended by current legislation. Among the results achieved has been the structuring of the following categories: Health Education Fragmentation Issues with evidence that the training of professionals is deficient in relation to mental health, the integrality and health care. The medicalization category Care and Life presents evidence that prescription drugs without monitoring is a trivial and central practice in the management of mental health users in APS. The Disarticulation Normative category between Mental Health and Primary Health Care: challenges for networks of training showed that professionals have a lack of clear guidance on how to handle cases of mental health and precariously articulate care networks. The category Set Speeches and Care Practices in Mental Health with Trends madhouse showed that there advance madhouse practices and the dismantling of the substitutive network by the state. We conclude that to build an overview of the main existing advances and retreats between the border field between mental health and primary care, it can be seen that the care practices in mental health in primary care have contradictory and dialectical dimensions, possible to identify the same teams progressive and retrogressive actions in relation to prescribing the Sanitary Reform and Psychiatry.